Effect of Treatment on the Physicochemical, Microbial and Sensory Properties of Tomato Powder - Amadou, Njoya Moyouwou; Yam, Semi Aphonsius; Che, Nde Sylvanus; Mathieu, Barbi (European Journal of Applied Sciences, 2024)
The purpose of this research aimed on the effect of various treatments on the physicochemical, microbial and sensory properties of tomato powder. Fresh tomatoes were pre-treated by sulphiting and blanching. After, they were dried (40; 50 and 60 °C) and milled. 06 tomato powder samples were then obtained. They were submitted to physicochemical (pH; titratable acidity; dry matter, vitamin C, and sugar), microbial (total bacterial, E.Coli and yeasts and mould) and sensory (colour, aroma, acidity and overall acceptability) analyses. The taste, colour, aroma, consistency and overall acceptability of tomato sauce prepared from the most 03 acceptable tomato powder samples were also evaluated. The vitamin C and sugar contents were not affected (p>0.05) by the treatment. The dry matter reduced (p<0.05) at high temperature (60 °C) after blanching while no effect was observed (p>0.05) by sulphiting. The pH was not affected (p>0.05) by the pre-treatment method. However, blanching decreased the pH with the increase of drying temperature although not significantly (p>0.05). At high temperature, there was a non-significant (p>0.05) reduction of titratable acidity after blanching in contrary to sulphiting where a significant increase (p<0.05) was achieved at 60 °C. All the tomato powder samples were appreciated similarly (p<0.05). The colour and the taste of the tomato powder sauce was not affected (p>0.05) by the treatment. The most appreciated sauce in term of aroma, consistency and overall acceptability was that from tomato powder blanched and dried at 50 °C. Blanching and drying tomato at 50 °C could represent one of appropriate methods for tomato powder production.